Identifying Pedagogical Design and Implementation of Synchronous Virtual Classrooms - Cilligol Karabey, Sinem; Karaman, Selcuk (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2024)
This study aimed to systematically compile the activities and applications to be used by instructors to conduct synchronous virtual classrooms effectively. Using specific keywords in various databases we examined the literature to discover the activities and applications associated with effective synchronous virtual classrooms. A total of 70 studies were included in the study, based upon pre-determined criteria. A total of 53 activities and applications for conducting synchronous virtual classrooms effectively were obtained and classified according to Gagné’s nine events of instruction (GNEI). These activities and applications were sorted within 11 themes dimensions: technical control, environment control, clarity, introductory activities, technological tools, course materials, interaction, feedback, summarizing, time management, and self-assessment. Synchronous virtual classrooms conducted according to this classification will serve as a guide for instructors to conduct synchronous virtual classrooms effectively.